Outcome of Laparoscopic Repair in Ventral Hernia - Nawaz Ali Dal, Arshad Hussain Abro, Zahid Ali Memon, Zeeshan Zia Qureshi, Nazneen Ali Khaskheli, Allah Rakhio Bhurgri (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the outcome of laparoscopic repair in ventral hernia. Study design: Prospective observational study. Place and duration of study: General Surgery Department of Tertiary Care Hospital, Liaquat University of Medical & Health Sciences (LUMHS), Jamshoro Sindh from 1st March 2017 to 30th June 2020. Methodology: Eighty six patients with ventral wall hernia were enrolled. Hernia was approached laterally and ports were placed from farther side of abdomen. In all cases three trocars were used one for 10mm and 2 ports for 5 mm. polypropylene mesh was used for hernia repair. Mesh was placed using intracorporeal mesh fixation technique. Results: The mean age of patients was 46±8.3 years. Fifty two (60.4%) were females and 34 (39.5%) were males. The ratio of females with ventral wall hernia is higher than males requiring surgery. The mean BMI of study participants was 30.8±4.3 kg/m2. Bowel perforation is characterized to be the most severe complications of laparoscopy and it affected 3.4% of the participants. The most common complication post-operatively was severe pain in 26.7% of patients, controlled by I/V pain killers for two to three days followed by seroma formation Conclusion: Laparoscopic ventral hernia repair is an excellent technique as compared to conventional techniques and has fewer complications but it requires surgical expertise and specific instruments. Although it is an ideal procedure for simple ventral wall hernias, it is not used for complex hernia. Key words: Laparoscopic repair, Ventral hernia, Mesh repair